The influence of improved acoustics on English First Additional Language teaching and learning in the Foundation Phase - Phatudi, Nkidi Caroline (University of Pretoria, 2018)
English First Additional language is introduced to the non-speakers of the language in Grade 1. This is in line with the Curriculum Assessment Policy Statement, which requires English to be introduced to Grade 1 learners irrespective of their home language or their language background (Department of Basic Education, 2012). To the majority of learners in South Africa, English is a second or a third language. Learning a new language poses numerous challenges, such as inability to decipher the sound system of the language. Moreover, primary school classrooms are known for being action filled and accommodative of what is known as "productive noise", which makes it difficult for Foundation Phase teachers to be audible to all learners in the classrooms. Options that are commonly used to reduce noise are hanging curtains and fitting tennis balls on the legs of chairs. This study focused on the use of a dynamic sound field amplification system as one way to improve acoustics in the classroom. The purpose of this study was to document the teachers’ experiences when using dynamic sound field amplification system. Although this study was not an intervention, the concept evaluation was used to understand teachers’ experiences and challenges as regards the background noise in their classrooms. This study was conducted in three Grade 1 mainstream classrooms where English First Additional Language is used for teaching and learning in the North West Province, South Africa. The classroom observations afforded me the opportunity to see how the learners reacted in the improved acoustic classroom. Lastly, the discussions with the teachers enabled me to hear how they feel about the use of the dynamic sound field amplified system. Components of the Programme Theory Evaluation with its relevance on change underpinned this study. For the purpose of this study I focused on the five steps or levels of theory of change i.e. inputs, activities, outputs, outcomes and impact (Evaluation Exchange, 2006). The practical application of the Programme Theory Evaluation guided the documentation of the teachers’ experiences. The use of dynamic sound field amplification system helped with the early identification of learning barriers and interventions in the three schools. This lessened the number of learners who were wrongly referred to special schools because of poor performance. Teachers’ health, high rates of absenteeism and voice fatigue were reduced, and classroom management was facilitated. The study found that the participants were not aware of the importance of acoustics in the classroom before dynamic sound field amplification system was introduced. They had to speak at the top of their voices and often repeated themselves for their learners to hear and understand. The dynamic sound field amplification system changed all that, the teachers’voices were amplified and that improved the acoustics in the three classrooms. The dynamic sound field amplification system is effective in the overcrowded classrooms where the background noise is normally high; it operates by amplifying the teacher’s voice relative to the background noise. The teacher’s amplified voice remains constant all the time and equally audible to all learners in the classroom at all the times. (DiSarno, Schowalter & Grass, 2002). The recommendations of this study are to share the information gathered from the three schools and the two district officials with the senior management of the North West Department of Education. They will be in the position to study the outcomes and assist schools accordingly by deciding if they see the importance of treating acoustics in the classrooms.